The toxicity of neostigmine against Aedes aegypti larvae - Kong, Sau, Mun
The yellow fever, dengue fever and chikungunya are the important mosquito-borne disease to human in the world. Aedes mosquitoes have been widely studied for its role as the vector for these diseases. Various larvicides have been introduced to control the mosquito population. Among all, temephos is the most popular and widely used . The frequent use of temephos has resulted in the development of resistance in field populations of Aedes mosquitoes in Malaysia. Thus, this study was carried out to explore the potency of utilizing Neostigmine Inj ection B.P. 2. 5 mg (neostigmine) as an alternative larvicide subsequently delaying the development of resistance of mosquitoes against temephos. The potency was evaluated by assessing the toxicity of neostigmine again st larvae of Ae. aegypti. Neostigmine is a drug used in the treatment for myasthenia gravis due to its effects as an anticholinesterase. The drug was chosen because of its mode of action, which is similar to organophosphate larvicide. In the study, four different dosages of neostigmine were evaluated, i.e. 12.5, 25, 50 and 100 ppm against the late third to early fourth instar larvae of Ae. aegypti using the modified WHO (1981) method. Temephos was included in the test regime as the benchmark and distilled water only as the control. The tests were conducted in five replicates for twenty-one days. The percentage of cumulative mortality of larvae was calculated and analyzed with Independent T test. The results showed 100 ppm of neostigmine has the highest percentage of mortality (99.2 %), followed by 50 (97.6 %), 12.5 (968 %) and 25 (94.4 %) ppm. The increase of mortality was significant (P < 0.05) for neostigmine at 100 ppm dosage compare to control. For treatment of 50 ppm of neostigmine, the increase of mortality was only significant at P < 0.10. However, when compared to temephos, the percentage of mortality generated by 100 ppm neostigmine was significantly (P < 0.05) lower. VIII.